The Role of Locus of Control: The Relationship Between Organizational Commitment and Job Insecurity In Desire To Switch - Zulkifli Sultan (STIE AMKOP, 2023)
The high number of employees who have the desire to change jobs is one of the causes of losses to the organization, so the purpose of this study was conducted to analyze the relationship between organizational commitment and job insecurity on the desire to move moderated by the variable locus of control. The research method used by researchers in this study is to use a quantitative descriptive approach, with data collection techniques distributing questionnaires to banking employees at the BRI Hertaning Branch Office, Makassar City. The sample used was 120 people with a saturated sampling technique, namely the number of populations that became the number of samples. The results of this study indicate that the organizational commitment variable has a significant negative effect on the intention to change jobs, while job insecurity has a positive effect on the intention to change jobs. In addition, the locus of control variable as a moderator variable is able to provide reinforcement of the relationship between organizational commitment and job insecurity on turnover intention.